Predictors of physical independence at discharge after stroke rehabilitation in a Dutch population. Issue 1 (March 2017) - Ten Brink, Antonia F.; Hajos, Tibor R.S.; van Bennekom, Coen; Nachtegaal, Janneke; Meulenbelt, Henk E.J.; Fleuren, Judith F.M.; Kouwenhoven, Mirjam; Luijkx, Marscha M.; Wijffels, Markus P.; Post, Marcel W.M.
Abstract : The aim of this study was to identify predictors, available at admission, of physical independence at discharge from inpatient rehabilitation. Secondary aims were to identify predictors of functional gain and length of stay (LOS). We included 1310 adult stroke patients who were admitted for inpatient rehabilitation in five Dutch rehabilitation centres. Data on the Utrecht Scale for Evaluation of Clinical Rehabilitation at admission and discharge (physical and cognitive independence, mood, pain and fatigue), age, sex and in a subsample stroke characteristics as well were collected. A prediction model was created using random coefficient analysis. None of the stroke characteristics were independently associated with physical independence or functional gain at discharge, or LOS. Higher physical and cognitive independence scores and severe pain at admission were predictors of higher physical independence scores at discharge. Furthermore, lower physical independence scores, higher cognitive independence scores, less pain at admission and younger age predicted more functional gain. Finally, lower physical and cognitive independence scores at admission and younger age predicted longer LOS. Physical independence at admission was the most robust predictor for rehabilitation outcome in a Dutch rehabilitation setting. To a lesser extent, age, cognitive independence and pain predicted rehabilitation outcome after stroke. Treatment of cognition and pain should be taken into account during rehabilitation. Further work needs to be carried out to establish whether focusing on these factors improves outcome after rehabilitation.